Energy Conservation Using Street Light Monitoring and Vehicle Vibrations for EV Charging - Dinesh Burande; Ravikant Nanwatkar; Omkar Kadam; Kalyani Kamble; Prajwal Thube; Shreyas Saraf; Piyush Dhamale (International Journal of Energy and Thermal Applications, 2025)
In the contemporary era, the escalating demand for sustainable energy solutions has prompted the exploration of innovative technologies to address energy conservation challenges. This research introduces a novel approach to energy conservation by integrating street light monitoring and utilizing vehicle vibrations for Electric Vehicle (EV) charging. The proposed system leverages smart sensors and advanced communication technologies to monitor street lights and harness vehicle vibrations, thereby contributing to the optimization of energy resources. The street light monitoring component involves the implementation of intelligent sensors and real- time data analytics to dynamically adjust the intensity of street lights based on environmental conditions and vehicular traffic. By autonomously regulating the luminosity of street lights, unnecessary energy consumption is minimized during periods of low activity, resulting in significant energy savings. Furthermore, the integration of vehicle vibrations as a source of energy for EV charging adds an additional layer of sustainability. Utilizing piezoelectric materials embedded in the road surface, the vibrations generated by passing vehicles are converted into electrical energy. This harvested energy is then stored and made available for electric vehicle charging stations strategically placed along roadways. The proposed system not only contributes to the reduction of energy consumption in street lighting but also addresses the growing need for sustainable solutions in the electric transportation sector. By combining these two innovative approaches, the research aims to create a synergistic effect that enhances overall energy efficiency and supports the widespread adoption of electric vehicles. The potential impact of this integrated system extends to urban planning, energy management, and the promotion of eco-friendly practices in smart cities.
Keywords: Lithium Ion Battery; Supercapacitor; cycling stability; e-bicycle; hybrid energy storage system